The influence of industrial clustering on climate change: An overview - Adejompo Fagbohunka (Economic and Environmental Studies (E&ES), 2015)
Climate change often referred to as global warming is one of the most important issues of the century, and is caused by many factors especially the activities emanating from industrial cluster. The paper therefore, underscores the influence of clustering on climate change. The paper adopts secondary sources of data; and has found out that despite the tremendous benefits of clustering in regional development, especially economic revamping, rejuvenation, overhauling and sustenance, it is not without some negative consequences. One of the major consequences is industrial pollution which has greatly increased atmospheric concentration of water vapour, methane, carbon-dioxide and nitrous oxide, all greenhouse gases which has significantly contributed to climate change. The paper further revealed the various consequences of global warming such as, large scale water and food shortages which can lead to catastrophic effects on wild life. Other consequence includes hurricane, droughts, heat waves and wild fire, changing ecosystem and acidifying ocean and other natural disaster. The paper has found out that, though clustering policy could be harnessed to launch a region into the desired goal of rapid industrialization; the negative impacts especially the emission of gases should be adequately curtailed by government through enacting environmental laws and regulations that promote sustainable industrial development. This could be achieved through the enforcement of pollution laws and control of the energy consumption of these industries. Nations should come together in order to provide solution to the problem of global warming.
Keywords: I15; 330; climate change; clustering; energy consumption; industrial pollution; sustainable industrial development